1987
DOI: 10.7863/jum.1987.6.7.389
|View full text |Cite
|
Sign up to set email alerts
|

Testicular microlithiasis. A unique sonographic appearance.

Abstract: Testicular microlithiasis, also known as intratubular tes,. ticular calcification, is a rarely encountered problem in urology. Now, with the easy availability of high-frequency real-time ultrasound scans, along with their exquisite resolution, sonographic evaluation of the scrotal contents has become an invaluable source of significant clinical information to urologists. We recently examined a patient with testicular microlithiasis; and we present here what we believe is the first report of the unique sonograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0
7

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 7 publications
2
67
0
7
Order By: Relevance
“…Testicular microlithiasis (TM), the presence of multiple small deposits of calcium within the testis, shows characteristic sonographic findings of multiple, intratesticular, nonshadowing echogenic foci. Since the original description of ultrasounddetected TM (Doherty et al, 1987), a number of studies have reported an association between TGCT and TM (Backus et al, 1994;Miller et al, 1996Miller et al, , 2006Cast et al, 2000;Bach et al, 2001;Bennett et al, 2001;Derogee et al, 2001;Middleton et al, 2002;Sakamoto et al, 2006). All the studies report ultrasound findings for men investigated for a suspect testicular pathology (infertility, hydrocele, varicocele or suspected tumour) and compare the rate of TM in men found to have TGCT with those that have other diagnoses, including normal testes.…”
mentioning
confidence: 99%
“…Testicular microlithiasis (TM), the presence of multiple small deposits of calcium within the testis, shows characteristic sonographic findings of multiple, intratesticular, nonshadowing echogenic foci. Since the original description of ultrasounddetected TM (Doherty et al, 1987), a number of studies have reported an association between TGCT and TM (Backus et al, 1994;Miller et al, 1996Miller et al, , 2006Cast et al, 2000;Bach et al, 2001;Bennett et al, 2001;Derogee et al, 2001;Middleton et al, 2002;Sakamoto et al, 2006). All the studies report ultrasound findings for men investigated for a suspect testicular pathology (infertility, hydrocele, varicocele or suspected tumour) and compare the rate of TM in men found to have TGCT with those that have other diagnoses, including normal testes.…”
mentioning
confidence: 99%
“…But it was not until the mid 80 s when Doherty et al using a 10-MHz transducer first described ultra sonically detected testicular microlithiasis [1]. Ever since, the interest in this entity has increased, with several case reports and retrospective studies reporting an association with testicular cancer [2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Ever since Doherty et al [1] described testicular microlithiasis on ultrasound scan in the late 80 s, the interest in this subject had been on the increase. However despite an association of testicular microlithiasis with testicular tumour [2][3][4][5][6][7][8] its aetiological role and the need for followup have remained largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…(1987) described a 23‐year‐old man, who at age 10 had an orchiopexy for cryptorchidism. By ultrasonography, a pattern of innumerable tiny bright echoes (‘white spots’) diffusely and uniformly scattered throughout the testis tissue was found.…”
Section: Introductionmentioning
confidence: 99%